Prevalence of internet addiction and its effects on lifestyle choices and snacking patterns in young adults - Spandana, B.; Prashanthi, Alam; Jamuna Rani, B.; Preethi, M. (International Journal Of Community Medicine And Public Health, 2025)
Background: The significant role of internet addiction in influencing dietary behaviour, particularly among young adults, has become a prominent cause for concern. The continuous connectivity provided by the internet, alongside the widespread use of social media and online platforms, has created an environment where individuals often find themselves deeply engrossed in virtual realms. This digital immersion frequently disrupts established routines, including eating habits. Methods: An exploratory study was conducted to examine the prevalence of internet addiction and dietary habits of young adults of 254 respondents. Data was collected using the Korean internet addiction scale (KS scale). The KS scale comprises demographic information, patterns of internet addiction, and lifestyle and snacking patterns. Statistical analysis done by SPSS. Results: The results of the study revealed that majority of the respondents were potential internet users (40.55%) followed by low risk (37.01%) and high risk (22.44%). Individuals at high risk exhibit markedly higher scores, reflecting more intense symptoms and reinforcing the need for specialized interventions tailored to this group. Conclusions: The study highlighted the concerning prevalence of internet addiction among young adults and its significant impact on dietary behaviours. With a substantial portion of respondents categorized as potential or high-risk users, it was evident that internet addiction disrupts traditional eating habits and routines. The findings underscore there is a need for targeted interventions aimed at addressing internet addiction, particularly among those at higher risk, to promote healthier dietary practices.